Exploring the causal links between cigarette smoking, alcohol consumption, and aneurysmal subarachnoid hemorrhage: a two-sample Mendelian randomization analysis - Lin, Heng; Yin, Yanqing; Li, Jie; Liu, Siwei; Long, Xiaoao; Liao, Zhuangbin (Frontiers in Nutrition, 2024)
Background Aneurysmal subarachnoid hemorrhage (aSAH) represents a critical health concern characterized by elevated mortality and morbidity rates. Although both genetic predisposition and lifestyle choices influence aSAH susceptibility, understanding the causative associations between cigarette smoking, alcohol consumption, and aSAH risk remains imperative. Mendelian randomization (MR) offers a robust methodological framework for dissecting these associations, leveraging genetic variants as instrumental variables. Objective In this study, a two-sample Mendelian randomization (TSMR) approach was employed to elucidate the causal connections between genetically determined cigarette smoking, alcohol consumption, and aSAH risk. Methods Genetic instruments associated with cigarette smoking and alcohol consumption were sourced from the genome-wide association study (GWAS) and Sequencing Consortium of Alcohol and Nicotine use (GSCAN). Using a genome-wide association study (GWAS) dataset that encompassed aSAH cases and controls of European ancestry, TSMR, which utilized the inverse variance weighting (IVW) method, was employed to estimate the causal effects. Rigorous criteria were applied for selecting instrumental variables to ensure a robust Mendelian randomization analysis. Results A significant causal association was found between genetically determined cigarette smoking and an increased risk of aSAH, with a 1-standard deviation (SD) increase in cigarette use genetically linked to a 96% relative risk elevation [OR-IVW = 1.96, 95% confidence interval (CI) = 1.28–3.01, p = 0.0021]. However, genetically determined alcohol consumption did not exhibit a statistically significant association with aSAH risk (OR-IVW = 1.22, 95% CI = 0.61–2.45, p = 0.578). Conclusion The Mendelian randomization analysis revealed a causal nexus between cigarette smoking and an increased risk of aSAH, advocating for targeted smoking cessation interventions within genetically predisposed cohorts. The results regarding the relationship between alcohol consumption and aSAH were affected by insufficient statistical power. A prudent interpretation of the findings highlights the limitations of Mendelian randomization in elucidating intricate genetic epidemiological relationships. Ongoing research involving larger cohort sizes and advanced methodological approaches is essential for comprehending the genetic underpinnings of aSAH.